The Oxford handbook of skepticism - Greco, John (Oxford handbooks., 2008)
In the history of philosophical thought, few themes loom as large as skepticism. Skepticism has been the most visible and important part of debates about knowledge. Skepticism at its most basic questions our cognitive achievements, challenges our ability to obtain reliable knowledge; casting doubt on our attempts to seek and understand the truth about everything from ethics, to other minds, religious belief, and even the underlying structure of matter and reality. Since Descartes, the defense of knowledge against skepticism has been one of the primary tasks not just of epistemology but philosophy itself.